2021
DOI: 10.1111/sed.12925
|View full text |Cite
|
Sign up to set email alerts
|

Statistical characterization of a confined submarine fan system: The Pennsylvanian Lower Atoka Formation, Ouachita Mountains, USA

Abstract: This manuscript is a preprint and has been submitted to Sedimentology for consideration for publication. As of September 28, 2020, this manuscript is under review and has not been accepted for publication. The content of subsequent versions may be different from this one. Once the manuscript is formally accepted, we will add the peer-reviewed publication DOI, through which the final version will be available. Should you have any feedback, please contact the corresponding author. We appreciate it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 101 publications
0
1
0
Order By: Relevance
“…It is worth noting that the submarine fan in this study exhibits a tongue-shaped morphology, which significantly differs from commonly developed fan shapes, indicating it is a typical confined fan. Previous studies have found a strong correlation between submarine fan shape and the degree of confinement in geomorphology (Sinclair and Cowie, 2003;Hou et al, 2022). As the degree of confinement in geomorphology increases, the corresponding submarine fan demonstrates a reduced lateral width and an extended longitudinal length, gradually transitioning from a fan-shaped to a tongue-shaped planar evolution (Liu et al, 2014;Zhang et al, 2016).…”
Section: Major Controlling Factors For the Evolution Of The Submarine...mentioning
confidence: 95%
“…It is worth noting that the submarine fan in this study exhibits a tongue-shaped morphology, which significantly differs from commonly developed fan shapes, indicating it is a typical confined fan. Previous studies have found a strong correlation between submarine fan shape and the degree of confinement in geomorphology (Sinclair and Cowie, 2003;Hou et al, 2022). As the degree of confinement in geomorphology increases, the corresponding submarine fan demonstrates a reduced lateral width and an extended longitudinal length, gradually transitioning from a fan-shaped to a tongue-shaped planar evolution (Liu et al, 2014;Zhang et al, 2016).…”
Section: Major Controlling Factors For the Evolution Of The Submarine...mentioning
confidence: 95%